Factors influencing purchase decisions on social media platforms: The role of explainable artificial intelligence - Dat, Nguyen Van; Dang, Pho Hai; Thich, Nguyen Van (Edelweiss Applied Science and Technology, 2025)
This study aims to measure the impact of privacy concerns and perceptions of personalization on purchase decisions on social media platforms. It focuses on the mediating role of attitudes toward advertising and the moderating role of Explainable Artificial Intelligence (XAI). The study investigates consumers who frequently shop on social media. The research model was implemented using an online questionnaire and direct interviews, yielding 515 valid responses. To assess the reliability of the measurement scales, SPSS 26 software was employed. The research hypotheses were tested, and the measurement and structural models were evaluated using AMOS 28. The proposed model is grounded in the Elaboration Likelihood Model (ELM), causal models, interpretability in human-AI interaction, computational privacy theory, and the Theory of Reasoned Action (TRA). The findings indicate that consumers’ perceptions of personalized advertising content positively influence their attitudes toward advertisements. Privacy concerns negatively affect users’ attitudes toward advertisements. Positive attitudes toward advertising, in turn, influence purchase decisions on social media. This study enriches the theoretical understanding of consumer behavior toward AI-enabled technological products and offers managerial implications for producers to enhance advertising quality and meet consumer demands in the context of social media shopping.